Gastric bypass does not normalize obesity‐related changes in ghrelin profile and leads to higher acylated ghrelin fraction12. (25th May 2013) - Barazzoni, Rocco; Zanetti, Michela; Nagliati, Carlo; Cattin, Maria Rosa; Ferreira, Clara; Giuricin, Michela; Palmisano, Silvia; Edalucci, Elisabetta; Dore, Franca; Guarnieri, Gianfranco; de Manzini, Nicolò
Abstract Objective: Gastric bypass (GBP) lowers food intake, body weight, and insulin resistance in severe obesity (SO). Ghrelin is a gastric orexigenic and adipogenic hormone contributing to modulate energy balance and insulin action. Total plasma ghrelin (T‐Ghr) level is low and inversely related to body weight and insulin resistance in moderately obese patients, but these observations may not extend to the orexigenic acylated form (A‐Ghr) whose plasma concentration increase in moderate obesity. Design and Methods: We investigated the impact of GBP on plasma T‐, A‐, and A/T‐Ghr in SO patients (n = 28, 20 women), with measurements at baseline and 1, 3, 6, and 12 months after surgery. Additional cross‐sectional comparison was performed between nonobese, moderately obese, and SO individuals before GBP and at the end of the follow‐up period. Results: Before GBP, SO had lowest T‐Ghr and highest A/T‐Ghr profile compared with both nonobese and moderately obese individuals. Lack of early (0‐3 months from GBP) T‐Ghr changes masked a sharp increase in A‐Ghr and A/T‐Ghr profile (P < 0.05) that remained elevated following later increments (6‐12 months) of both T‐ and A‐Ghr (P < 0.05). Levels of A‐Ghr and A/T‐Ghr at 12 months of follow‐up remained higher than in matched moderately obese individuals not treated with surgery (P < 0.05). Conclusions: The data show that following GBP, early T‐Ghr stability masks elevation of A/T‐Ghr, that is stabilized after later increments of both T‐ and A‐hormones. GBP does not normalize the obesity‐associated elevated A/T‐Ghr ratio, instead resulting in enhanced A‐Ghr excess. Excess A‐Ghr is unlikely to contribute to, and might limit, the common GBP‐induced declines of appetite, body weight, and insulin resistance.